High temperature fluidized bed zero valent iron process for flue gas nitrogen monoxide removal. Issue 3 (7th March 2008) - Cheng, Chih-Yu; Chen, Shiao-Shing; Tang, Chih-Hui; Chang, Yu-Min; Cheng, Hsu-Hui; Liu, Hsuan-Liang
Abstract : A fluidized bed zero valent iron (ZVI) reactor was designed for nitrogen monoxide (NO) removal with typical flue gas temperatures based on ZVI's strong reducing abilities. Three different parameters: temperature, influent concentration, and ZVI dosage were tested. Higher NO removals were observed for higher temperature, which was contributed to either higher diffusivity for NO or higher rate constant at higher temperature instead of thermodynamic aspect, since enthalpy change of the chemical reaction (Δ H ) is negative and equilibrium constant is decreased when temperature is increased. At the same temperature, ZVI capacities (as mg NO/g ZVI) were constant for both influent concentration and ZVI dosage variation. Activated energies were determined for two different stages: before and after breakthrough. Before breakthrough, excess ZVI was presented and the reaction was described as a pseudo-first order reaction, and the activated energy ( E a ) for the first stage was calculated as 46.5 kJ/mol according to the Arrhenius equation. After breakthrough, the presence of ZVI was not in excess and the reaction order of ZVI and NO was considered as 2nd order (1 order in [NO] and 1 order in ZVI), and E a was determined to be 7.5 kJ/mol.